2004
DOI: 10.1128/aem.70.2.1031-1039.2004
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of the lys7 Gene, Encoding Saccharopine Reductase in Penicillium chrysogenum , Leads to Accumulation of the Secondary Metabolite Precursors Piperideine-6-Carboxylic Acid and Pipecolic Acid from α-Aminoadipic Acid

Abstract: Pipecolic acid serves as a precursor of the biosynthesis of the alkaloids slaframine and swainsonine (an antitumor agent) in some fungi. It is not known whether other fungi are able to synthesize pipecolic acid. Penicillium chrysogenum has a very active ␣-aminoadipic acid pathway that is used for the synthesis of this precursor of penicillin. The lys7 gene, encoding saccharopine reductase in P. chrysogenum, was target inactivated by the double-recombination method. Analysis of a disrupted strain (named P. chry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Although the targeting efficiency obtained is less than in a DPcku70 strain (Hoff et al, 2009) the observed frequencies of homologous recombination are clearly above values that were observed with the wild-type strain (e.g. Casqueiro et al, 1999;Hoff et al, 2009;Naranjo et al, 2004;Snoek et al, 2009). The use of the non-integrative RNAi vector leads to the construction of single and double mutants that will be a valuable tool for further functional and physiological studies.…”
Section: Discussionmentioning
confidence: 90%
“…Although the targeting efficiency obtained is less than in a DPcku70 strain (Hoff et al, 2009) the observed frequencies of homologous recombination are clearly above values that were observed with the wild-type strain (e.g. Casqueiro et al, 1999;Hoff et al, 2009;Naranjo et al, 2004;Snoek et al, 2009). The use of the non-integrative RNAi vector leads to the construction of single and double mutants that will be a valuable tool for further functional and physiological studies.…”
Section: Discussionmentioning
confidence: 90%
“…3). Later on, this group observed the accumulation of pipecolic acid (along with P6C) upon inactivation of the gene encoding saccharopine reductase, and its origin was determined to be from a-AAA instead of lysine through comparison of the intracellular accumulation of pipecolic acid with another mutant which lacks a-AAA reductase [55]. Here, pipecolic acid appeared to be an incidental intermediate in lysine biosynthesis, derived from the spontaneous chemical equilibrium of a-AAA-semialdehyde into P6C, and the easy conversion of P6C to pipecolic acid (probably catalyzed by the universally existing P5C reductase).…”
Section: A-aminoadipic Acid Pathwaymentioning
confidence: 98%
“…It has been reported that P. chrysogenum has a very active alpha-aminoadipic acid pathway, which is used for the synthesis of this precursor of penicillin [26]. Saccharopine reductase (SR), an enzyme of the α-aminoadipic acid pathway of lysine biosynthesis in fungus, is involved in lysine degradation pathway to produce aminoadipate, which serves as a key intermediate in the biosynthesis of lysine and penicillin in β-lactam-producing fungi [27].…”
Section: Discussionmentioning
confidence: 99%